Jarcho-Levin syndrome term baby with recurrent apnea - Devadas, Sahana; Govindarajan, Varun; Hanumanna, Anil Kumar; Gowda, Chethana; Kariyappa, Mallesh (International Journal of Contemporary Pediatrics, 2021)
Jarcho-Levin syndrome or spondylocostal dysostosis, is a rare axial skeleton anomaly due to mutation in genes involved in somitic segmentation during embryogenesis. We describe a term, newborn baby with antenatally detected midthoracic lordotic deformity with skeletal features of multiple rib anomalies and vertebral defects, but with normal limb lengths. Baby had recurrent apnea requiring non-invasive ventilation and was successfully weaned to room air within 2 days. This syndrome is underdiagnosed and we wish to highlight the simple process involved in making a clinico-radiological diagnosis.